Effect of Rubus Occidentalis Extract on Metabolic Parameters in Subjects with Prediabetes: A Proof‐of‐concept, Randomized, Double‐blind, Placebo‐controlled Clinical Trial. (9th June 2016) - An, Jee Hyun; Kim, Dong‐Lim; Lee, Tae‐Bum; Kim, Kyeong Jin; Kim, Sun Hwa; Kim, Nam Hoon; Kim, Hee Young; Choi, Dong Seop; Kim, Sin Gon
Abstract : Rubus occidentalis (RO) has beneficial effects on glucose and lipid profiles in vitro . The aim of the study was to investigate RO extract effect on metabolic parameters in prediabetic patients, adopting a 12‐week, randomized, double‐blind, placebo‐controlled trial. Forty‐four patients (age 59.0 ± 8.2 years, 70.5% females, HbA1c 5.8 ± 0.4%) were divided into placebo ( n  = 13), low‐dose RO extract (LRE; n  = 14), or high‐dose RO extract (HRE; n  = 17) groups. Either 900 or 1800 mg per day of RO extract was administered orally. Area under the curve for glucose obtained 2 h after a 75‐g oral glucose tolerance test was significantly decreased in the HRE group, compared with the placebo group (−28.1 ± 42.4 vs. +13.4 ± 52.6 mg/dL, p  < 0.05). Homoeostasis model assessment‐B was increased (+17.11 ± 10.69, +5.24 ± 4.10, and +0.86 ± 6.01 in HRE, LRE, and placebo, respectively, p  < 0.05). Serum levels of monocyte chemoattractant protein‐1 and oxidized low‐density lipoprotein were significantly decreased by treatment in a dose‐dependent manner (monocyte chemoattractant protein‐1: −35.0 ± 21.2, +8.4 ± 18.1, and +24.2 ± 14.5; oxidized low‐density lipoprotein: −19.7 ± 8.5, −13.1 ± 7.2, and −2.2 ± 11.0 in the HRE, LRE, and placebo, respectively, p  < 0.05). The results support the beneficial effects of RO extract on the control of glycemia and vascular inflammation in prediabetic patients. (ClinicalTrials.gov: NCT01964703). Copyright © 2016 John Wiley & Sons, Ltd.